MAINTAINING THE GOOD IMAGE OF A PUBLIC FIGURE THROUGH THE USE OF REPUTATION MARKETING - Anathasia Citra (President University, 2018)
ABSTRACT. This study aims to look at the application of the application of Reputation Marketing by a PublicFigure in maintaining a good image. How does the use of Reputation Marketing in the entertainment industry canaffect the continuity of the career of a Public Figure. The careers of a Public Figure who work in the entertainmentindustry is very vulnerable, if marketing strategies and maintain a good self image are not implemented. Thisstudy takes Hilbram Dunar as the subject. He works as a television host, radio host,MC, entertainer and authorwho began his career in 1996, while maintaining good image to date. With the concept of Reputation Marketing,author examined his personal branding, personal and social life to his choice of words and topics in social media.This research will contribute ideas to the study of communication with the subject about the image, personalbranding, reputation marketing and reputation marketing in the era of internet, and provide practical ideas forpublic figures who work in the entertainment industry. This research is a descriptive study with a qualitativeapproach. The results of this study found that the application of Reputation Marketing is very appropriate tomaintain a good image of a Public Figure who works in the entertainment industry. With the development oftechnology, especially the new media such as the various social media such as twitter and path, a public figuremust have his own positioning of the image that he wants to convey to the public and must maintain consistency.In addition, there are things that must be avoided in order to maintain reputation. Reputation is important for thecareer of a Public Figure and good image is not easy to maintain. The application of Reputation Marketing forPublic Figure has the same function like a product, which is for generating profit. A good image of a PublicFigure becomes a commodity which will have an impact on the sustainability of his career.